Authority of the Indonesian National Army in Prevention and Eradicatiion - Syafei, Imam; Marwan (Journal of Law, Politic and Humanities, 2025)
The purpose of analyzing and finding the form of terrorism that is the authority of the Army in preventing and eradicating it. This research is a normative legal research, to determine the differences and similarities between the legal systems of one country and another. Comparison of Indonesia and Malaysia. In the procedure for handling cases of terrorism crimes in accordance with Law Number 15 of 2003, it must be carried out by state institutions that are given authority with a full sense of responsibility and seriousness. Both from the TNI, Police and State Intelligence Agency in the context of the investigation and arrest process which both support the smoothness of the investigation process that will be held later. The use of military force to combat terrorism is not taboo, both from a domestic political perspective, in the context of the international humanitarian law framework, and the provisions of the Charter and various UN resolutions. The TNI as a state defense tool, functions as a deterrent against every form of military threat and armed threat from outside and within the country against the sovereignty, territorial integrity, and safety of the nation. Such provisions are in line with what is formulated in Article 30 Paragraph (2) of the 1945 Constitution which reads, "The defense and security efforts of the state are carried out through the total people's defense and security system by the Indonesian National Army and the Republic of Indonesia Police as the main force, and the people as supporters." Law Number 3 of 2002 concerning National Defense states that the position of the TNI is the main component in the state defense system in order to carry out defense tasks in Indonesia. Based on these provisions, the TNI has the authority to eradicate terrorism, especially in carrying out duties to protect the safety of the nation and most importantly as a peacekeeper both nationally and internationally. The participation of the TNI in eradicating terrorism is a preventive effort. The TNI, which is part of society and the nation, has the same responsibility in fighting terrorism. The involvement of the TNI in handling acts of terrorism needs to find a way out and clear legal instruments, namely whether the TNI is the main component, reserve component or supporting component so as not to conflict with the principle of due process of law.